Saint Louis, King of France. Engraving. - Auteur inconnu (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Saint Louis, King of France. Engraving.. Saint Louis, King of France. Engraving. Iconographic Collections
Droits : Licence Creative Commons Attribution 4.0 via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie